Eight-graders’ mathematical literacy on Percentage Problem - Ihsan, Hisyam; Alimuddin, Alimuddin; Alimuddin, Fauziyyah (Jurnal Ilmiah Wahana Pendidikan, 2024)
Mathematical literacy involves mastery of concepts, procedures, and critical and creative thinking in applying mathematical knowledge to everyday life problems. The study examined the mathematical literacy used by 36 students for the percentage problems. The students were invited to solve two kinds of percentage problems called Best Buy and Savings Over problems. There are four response categories for correct answer, one for reasonable response, and two categories for incorrect answers. Analysis of the responses showed that at least half of the students understood that they could not compare percentages without considering what the percentages represented. The majority of this group solved the problem explicitly by showing that the answer depends on the list price. Some students did this indirectly by taking examples of items that had the same list price or nominal value in both stores and then performing the calculations. About half of the students compared the two percentages as absolutes. The other students proceeded in the same way but came to the wrong conclusion. This raises the issue of evaluating these responses. Although the correct answers were not given, it is clear that these students knew that the percentages were related to something. These responses were not scored as “approximately correct reading” or “performing the task correctly,” but they were still considered and rewarded as reasonable responses. Keywords: Mathematical Literacy, Percentage Problem